Imported cutaneous leishmaniasis caused by Leishmania major in a Chinese laborer who worked in Saudi Arabia - Min Zhang; Fang Liu; Haibo Liu; Wenxing Hu; Hong Sang (Sociedade Brasileira de Dermatologia, 2016)
Abstract: We report an imported case of cutaneous leishmaniasis in a 37-year-old man from Saudi Arabia caused by Leishmania major. He presented with non-healing nodulo-ulcerative lesions with a "volcanic crater" on the lower limbs. It was clearly cutaneous leishmaniasis - a rare disease in China - as reflected by the patient's clinical history, the lesions' morphology, histopathological examination, culture and PCR analysis of the lesions. The patient was completely cured after two cycles of sodium stibogluconate treatment. This case report demonstrates that dermatologists should be aware of sporadic cutaneous leishmaniasis cases in non-endemic areas.